Comparison of gravity-resisted and gym-based core training on core endurance - Van der Merwe, F. H.; Burden, S. B.; Maulder, P. S. (South African Journal for Research in Sport, Physical Education and Recreation, 2017)
Conditioning specialists have been incorporating concepts of gravity-resisted core training, both on stable and unstable surfaces, to enhance core endurance despite limited empirical evidence. The purpose of this study was to compare the effects of gravity-resisted and gym-based core training on core endurance. The experimental group (n=8) followed a gravity-resisted core training intervention while the control group (n=8) followed a gym-based core training intervention incorporating similar exercises over a 6-week period. Pre- and post-testing consisted of an isometric prone bridge endurance test, dominant and non-dominant isometric side flexor endurance tests, an isometric trunk flexor endurance test and an isometric trunk extensor endurance test. Relative to the control group, the experimental group showed a very likely improvement in isometric trunk flexor endurance (33.7±18.3%, 90% Confidence limits), likely improvements in isometric non-dominant side flexor endurance (26.1±18.7%), isometric prone bridge endurance (22.4±13.9%), and isometric dominant side flexor endurance (30.4±27.7%). Using a gravity-resisted core training intervention is likely to produce beneficial gains in core endurance for resistance trained males to a greater extent than a programme of similar exercises conducted conventionally in a gym